2012
DOI: 10.1371/journal.pone.0047467
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Contributions of Basal Ganglia and Hippocampus to Spatial Navigation Using Reinforcement Learning

Abstract: A computational neural model that describes the competing roles of Basal Ganglia and Hippocampus in spatial navigation is presented. Model performance is evaluated on a simulated Morris water maze explored by a model rat. Cue-based and place-based navigational strategies, thought to be subserved by the Basal ganglia and Hippocampus respectively, are described. In cue-based navigation, the model rat learns to directly head towards a visible target, while in place-based navigation the target position is represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Vagus nerve stimulation enhances extracellular hippocampal NE levels, which could be at least partly responsible for its seizure-suppressing effect in the intrahippocampal pilocarpine rat model (Raedt et al, 2011). Monoaminergic neurons and their projection fibers are not only found in the cortex, striatum and thalamus, but also in the hippocampus (Joels and Baram, 2009; Sukumar et al, 2012). In addition, monoaminergic control of neurogenesis in the adult midbrain (salamander) and hippocampus (rodents) have been suggested (Park and Enikolopov, 2010; Berg et al, 2011).…”
Section: Slc18 Familymentioning
confidence: 99%
“…Vagus nerve stimulation enhances extracellular hippocampal NE levels, which could be at least partly responsible for its seizure-suppressing effect in the intrahippocampal pilocarpine rat model (Raedt et al, 2011). Monoaminergic neurons and their projection fibers are not only found in the cortex, striatum and thalamus, but also in the hippocampus (Joels and Baram, 2009; Sukumar et al, 2012). In addition, monoaminergic control of neurogenesis in the adult midbrain (salamander) and hippocampus (rodents) have been suggested (Park and Enikolopov, 2010; Berg et al, 2011).…”
Section: Slc18 Familymentioning
confidence: 99%
“…It is well known that coupled excitatory-inhibitory pools of neurons can exhibit rich dynamic behavior like oscillations and chaos (Borisyuk et al, 1995 ; Sinha, 1999 ). This hypothesis has inspired models simulating various BG functions ranging from action selection in continuous spaces (Krishnan et al, 2011 ), reaching movements (Magdoom et al, 2011 ), spatial navigation (Sukumar et al, 2012 ), precision grip (Gupta et al, 2013 ), and gait (Muralidharan et al, 2013 ) in normal and Parkinsonian conditions. Using a network of rate-coding neurons, Kalva et al ( 2012 ) showed that exploration emerges out of the chaotic dynamics of the STN-GPe system (Kalva et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…After DA diffuses across the junction and binds with receptors expressed on the postsynaptic neuron, the activated receptors induce changes in the activity of the postsynaptic neuron. Recent postmortem and imaging studies have found that monoamine neurons and their projection fibers are located not only in the cortex, striatum, and thalamus but also in the hippocampus (Joels and Baram, ; Sukumar et al, ). Dopamine and serotonin (5‐HT) system dysregulation by the hippocampus has implications for the pathophysiology and treatment of mental or affective disorders (Grace, ; Kobayashi et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%